Diversified Regulation of Cytokinin Levels and Signaling During Botrytis cinerea Infection in Arabidopsis - Li, Beibei; Wang, Ruolin; Wang, Shiya; Zhang, Jiang; Chang, Ling (Frontiers in Plant Science, 2021)
Cytokinins (CKs) can modulate plant immunity to various pathogens, but how CKs are involved in plant defense responses to the necrotrophic pathogen Botrytis cinerea is still unkown. Here, we found that B. cinerea infection induced transcriptional changes in multiple genes involved in the biosynthesis, degradation and signaling of CKs, as well as their contents, in pathogen-infected Arabidopsis leaves. Among the CKs, gene expression of oxidase/dehydrogenase 5 (CKX5) was remarkably induced in the local infected leaves and the distant leaves of the same plant without pathogen inoculation. Cis-zeatin (cZ) and its riboside (cZR) accumulated considerably in infected leaves, suggesting an important role of cis-zeatin type of CKs in the plant response to B. cinerea. Cytokinin double-receptor mutants were more susceptible to B. cinerea infection, whereas an exogenous CK treatment enhanced the expression levels of defense-related genes, resulting in higher resistance of Arabidopsis to B. cinerea. Investigation of CK responses to B. cinerea infection in a jasmonic acid (JA) biosynthesis mutant, jar1-1, and the ethylene (ET)-insensitive mutant, ein2-1, showed that CK signaling and CK levels, namely those of isopentenyladenine (iP), isopentenyladenine riboside (iPR) and trans-zeatin (tZ), were enhanced in jar1-1's infected leaves. By contrast, reductions in the iP, iPR, tZ, tZ riboside (tZR) as well as cZR contents occurred in ein2-1's infected leaves, whose transcript levels of CK signaling genes were likewise differentially changed. The type-A response regulator gene ARR5 of CKs were up-regulated in infected leaves of ein2-1 whereas another type-A response regulator, ARR16, was significantly down-regulated, suggesting the existence of a more complex regulation of CK signaling via the ET pathway. Accumulation of cis-zeatin type of CKs in B. cinereainfected leaves depended on ET but not JA levels. Collectively, our findings provide evidence that CK responds to B. cinerea infection in a variety of ways that are differently modulated by JA and ET pathways in Arabidopsis.